Trust and Digital Marketing: Impact on Online Fashion Purchasing Decisions: Kepercayaan dan Pemasaran Digital: Dampak pada Keputusan Pembelian Fashion Online - Elis Okta; Rita Ambarwati (Universitas Muhammadiyah Sidoarjo, 2022)
This study investigates the impact of product quality, product price, trust, and digital marketing on online purchasing decisions for fashion products. Using a quantitative research design and SmartPLS software, data was collected from 100 respondents through questionnaires at Qiyara boutique in Sidoarjo. Findings reveal that while product quality and price have a positive relationship, they do not significantly influence online purchasing decisions. However, trust and digital marketing demonstrate significant positive associations with online purchasing decisions. These results highlight the importance of building trust and implementing effective digital marketing strategies to enhance online fashion purchasing decisions. The implications of this study contribute to the understanding of consumer behavior in the context of online fashion retailing, assisting practitioners in developing strategies that can increase customer engagement and satisfaction. Highlights: Trust and Digital Marketing: This study explores the influence of trust and digital marketing on online purchasing decisions for fashion products. Non-significant Impact of Product Quality and Price: Findings indicate that product quality and price have positive but non-significant relationships with online purchasing decisions for fashion products. Significance of Trust and Digital Marketing: The study reveals that trust and effective digital marketing strategies significantly impact online fashion purchasing decisions, emphasizing their importance in driving consumer behavior. Keywords: Trust, Digital Marketing, Online Fashion, Purchasing Decisions, Path Analysis